Recent Advances in Oral Peptide or Protein-Based Drug Liposomes - Jian Cui; Zhiwei Wen; Wei Zhang; Wei Wu (MDPI AG, 2022)
The high physiology and low toxicity of therapeutic peptides and proteins have made them a hot spot for drug development in recent years. However, their poor oral bioavailability and unstable metabolism make their clinical application difficult. The bilayer membrane of liposomes provides protection for the drug within the compartment, and their high biocompatibility makes the drug more easily absorbed by the body. However, phospholipids-which form the membranes-are subjected to various digestive enzymes and mucosal adhesion in the digestive tract and disintegrate before absorption. Improvements in the composition of liposomes or modifying their surface can enhance the stability of the liposomes in the gastrointestinal tract. This article reviews the basic strategies for liposome preparation and surface modification that promote the oral administration of therapeutic polypeptides.